The Islamic Economics Philosophy And Application Reality In The Existing Islamic Economic Activities In The World - Abul Bashar Bhuiyan; Abdul Ghafar Ismail; Mohd Zakhiri Bin Nor; Md. Jafor Ali; Mohammad Solaiman (Centre for Research on Islamic Banking & Finance and Business, 2024)
Non-Indexed Publication